Advanced procedures for pain management : a step-by-step atlas - Aló, Kenneth M. (Springer, 2018)
Edited by Sudhir Diwan, a former Director of Pain Medicine fellowship program at Ivy League Weill Cornell Medical College, and Timothy R. Deer, an internationally renowned expert in neuromodulation and minimally invasive spinal procedures, this atlas covers advanced procedures that normal residency and fellowship programs may not cover. It consolidates information pain fellows usually amass by traveling throughout the country to various specialized weekend courses. Advanced Procedures for Interventional Pain Management: A Step-by-Step Atlas is for physicians that know the fundamentals of pain medicine and want to push their knowledge further. Through easy-to-digest bullet points, extensive diagrams, hundreds of ﬁgures, and expanded legends beneath each illustration, this compendium covers techniques such as ﬂuoroscopic guidance and radiation safety, endoscopic transforaminal discectomy, endoscopic direct-percutaneous discectomy, transforaminal myelogram, percutaneous facet fusion, percutaneous sacroplasty, vertebral augmentations, percutaneous tumor ablation, percutaneous spinal fusion, minimally invasive spinal decompression (MILD), Interspinous Spacer Placement and advanced neuroaugmentation techniques like high frequency stimulation and DRG stimulation. This book also has a dedicated section on Regenerative Medicine with chapters on platelet rich plasma, stem cell therapy, and intradiscal regenerative therapy. Each chapter has a strict chapter format that includes the indications and contraindications for each procedure, a list of equipment and drugs, a step-by-step illustration-focused how-to, a list of possible post-procedural complications, and bullet-pointed clinical pearls and pitfalls. Within each chapter the authors will also cover the variations of each procedure due to diﬀerent equipment. This book is ideal for pain medicine fellows, spine surgeons, and interventional pain...